EVALUATING THE IMPACT OF STARBOOKS TRAINING EXTENSION PROGRAM: A BASIS FOR PROGRAM ENHANCEMENT - Farren, May Lynn M.; Ojeno, Vexter Jeff E.; Yumen, Nolan M. (Transpublika Publisher, 2024)
The Community Empowerment through Science and Technology (CEST) program, led by the Department of Science and Technology (DOST), aims to address educational inequalities in underserved communities through strategic science and technology (S&T) interventions. One of key initiatives, the STARBOOKS training extension program, provides offline access to critical STEM resources, empowering rural schools with minimal connectivity. Implemented at Mag-Aba National High School in Pandan and Sebaste High School in Sebaste, the program targets enhanced digital literacy and equitable resource distribution. This study evaluates the STARBOOKS program impacts on teaching practices, student learning outcomes, and its overall contribution to bridging the digital divide in rural educational settings. It identifies program benefits, application of skills, challenges encountered, and enhancement recommendations. A mixed-methods approach was used, integrating quantitative surveys of 40 teachers and 80 students with qualitative insights gathered through open-ended questions. Data analysis employed descriptive statistics for quantitative data and thematic analysis for qualitative responses. Findings revealed that 85% of participants rated the program as highly beneficial. STARBOOKS was most utilized in STEM subjects, with notable applications in Filipino, Literature, and Entrepreneurship. Teachers reported improved lesson planning and classroom engagement, while 78% observed enhanced student academic performance. Key challenges included limited device availability (65%) and insufficient training (45%), highlighting areas requiring targeted interventions. The STARBOOKS program demonstrates significant potential in fostering equitable education and digital literacy. Recommendations include expanding program access, enhancing teacher training, increasing device availability, and introducing interactive STEM activities. Structured monitoring and evaluation systems are essential for sustaining program impact.